PROBLEMATIK YURIDIS TERHADAP JASA ADVOKAT DALAM UNDANG-UNDANG ADVOKAT - Zai, Fransiskus Rahmad; Ghozali, Elizabeth; Tamba, Pandapotan (Ensiklopedia of Journal, 2024)
The advocate profession is a profession that provides legal services to clients in the form of providing legal advice and/or legal assistance as well as being a legal representative who acts for and on behalf of and in the client's legal interests. Therefore, advocates have the right to receive an honorarium for legal services provided to their clients, the amount of which is determined fairly based on an agreement between the advocate and their client in accordance with the provisions of Article 21 paragraph (2) of the Advocate Law. The arrangement for advocate services shows that the advocate's honorarium is entirely the result of negotiations between the advocate and the client, without limits. The lack of standardization of the regulation of advocate services in the Advocate Law can give rise to several legal problems, including: 1) the cost of legal services becomes expensive, making it quite burdensome for justice seekers; 2) the emergence of disputes or disputes between advocates and clients which result in lawsuits in court; 3) has the potential to become a means of money laundering.Keywords: Advocate, Honorarium